THE REVIEW OF CORRUPTION ERADICATION IN INDONESIA BASED ON THE ASPECT OF JURIDICAL, MORALITY, AND IDEOLOGY OF PANCASILA - SURYANINGSI; THARUNA QALIS MULA (Sekolah Tinggi Ilmu Hukum Awang Long, 2020)
This article proposes to review the handling of corruption cases judicially, morality, and by the ideology of Pancasila in Indonesia. This study is normative legal research with descriptive analysis. This study uses the philosophical approach and the concept approach to find out efforts carried out by the government to tackle corruption in Indonesia from the juridical and moral aspects of the Indonesian people based on the Pancasila Ideology. The corruption eradication efforts have not been able to be resolved optimally because it is having been spread sporadically in Indonesia. Obstacles are on structural, cultural, instrumental and management aspects. The prevention and eradication of corruption must be emphasized as a moral responsibility of the Indonesian people. Because it will be one of the biggest threats to the existence of the Indonesian nation. Corruption prevention must be carried out systematically by strengthening regulations and conducting international cooperation in making the issue of corruption as a crime against Human Rights throughout the world, especially in Indonesia. The aspect of law enforcement in eradicating criminal acts of corruption requires the role of all parties involved in achieving the target in the eradication of corruption that have become an epidemic in Indonesia, there are four factors causing corruption; political and judicial factor, historical factor, social and cultural factor, and the economy factor. Concrete solutions in eradicating corruption needed by Indonesia are redesigning public services, strengthening transparency, supervision and sanctions on government activities related to the economy and human resources, increasing the empowerment of supporting instruments in preventing corruption and to make sure law enforcers are free of corruption. Corruption eradication strategy must be built with the willingness of all parties who want to eradicate corruption itself, by not giving the slightest tolerance in the corrupt acts themselves. In realizing an effort to eradicate corruption itself, it takes a determination in fulfilling the prerequisites in terms of being driven by political ability and will and strong commitment from all parties, transparent and accountable in its implementation, available and balanced resources and capacities.